Gerakan Teman Sebaya Sadar Bahaya NAPZA : Edukasi, Pendampingan dan Pengenalan Rapid Test Urine di SMK Kesehatan Bali Khresna Medika - Bintari, Ni Wayan Desi; Prihatiningsih, Diah; Widana, A.A.G. Oka; Purwanti, Ika Setya (Penerbit Widina, Widina Media Utama, 2025)
Abuse of drugs, psychotropics, and other addictive substances among adolescents is a problem that requires attention and support from various parties. The peer model is one of the potential programs to be activated in the school environment in implementing peer counseling. Peers will act as role models who are able to convey information related to drug abuse to their peers. This community service was carried out at the Khresna Bali Medika Health Vocational School with an implementation period of December 2024-January 2025. The implementation of activities was in the form of providing education related to the types of drugs and their abuse, peers and health promotion that must be carried out related to drug abuse and rapid urine test examinations for early detection of drug abuse. The results of community service can increase students' knowledge regarding the types of drugs and their abuse and health promotion that can be carried out. The pre-test results showed that students' knowledge was good at 33.33%, sufficient at 25% and lacking at 41.67%. After being given education, all students (100%) already had good knowledge regarding the types and abuse of drugs and health promotion that can be carried out. In addition, students as potential peers have also been able to explain again the dangers of drug abuse to their peers in the simulation session. In this activity, a demonstration was also carried out regarding drug examinations using the strip test method which was followed by all community service participants.ABSTRAKPenyalahgunaan narkoba, psikotropika dan zat adiktif lainnya (NAPZA) di kalangan remaja merupakan permasalahan yang perlu perhatian dan dukungan dari berbagai pihak. Model teman sebaya merupakan salah satu program yang potensial digiatkan di lingkungan sekolah dalam pelaksanaan konseling sebaya. Teman sebaya akan berperan sebagai role model yang mampu menyampaikan informasi terkait penyalahgunaan NAPZA bagi rekan sebayanya. Pengabdian kepada masyarakat ini dilakukan di SMK Kesehatan Khresna Bali Medika dengan periode pelaksanaan Desember 2024- Januari 2025. Pelaksanaan kegiatan berupa pemberian edukasi terkait jenis NAPZA dan penyalahgunaannya, teman sebaya dan promosi kesehatan yang harus dilakukan terkait penyalahgunaan NAPZA dan pemeriksaan rapid test urine untuk deteksi dini penyalahgunaan narkoba. Hasil pengabdian masyarakat dapat meningkatkan pengetahuan siswa terkait jenis NAPZA dan penyalahgunaannya serta promosi kesehatan yang dapat dilakukan. Hasil pre test menunjukkan bahwa pengetahuan siswa baik sebanyak 33,33%, cukup sebanyak 25% dan kurang sebanyak 41,67%. Setelah diberikan edukasi seluruh siswa (100%) sudah memiliki pengetahuan yang baik terkait jenis dan penyalahgunaan NAPZA dan promosi kesehatan yang dapat dilakukan. Selain itu siswa sebagai calon teman sebaya juga sudah mampu menjelaskan kembali terkait bahaya penyalahgunaan NAPZA kepada rekan sesamanya pada sesi simulasi. Pada kegiatan ini juga dilakukan demonstrasi terkait pemeriksaan narkoba dengan metode strip test yang diikuti oleh seluruh peserta pengabdian.